2020
DOI: 10.1038/s41598-020-64940-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a pro-healing stent in an animal model of early neoatherosclerosis

Abstract: Background: neoatherosclerosis represents an accelerated manifestation of atherosclerosis in nascent neointima after stenting, associated with adverse events. We investigated whether improved reendothelialization using RGD-coated stents results in diminished vascular permeability and reduced foam cell formation compared to standard DeS in atherosclerotic rabbits. Methods and Results: neointimal foam cell formation was induced in rabbits (n = 7). Enhanced endothelial integrity in RGDcoated stents resulted in de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Joner et al investigated whether cyclic arginine-glycine-aspartic acid (cRGD)-coated stents that targeted integrin α v β 3 could increase the adhesion of ECs as well as elevate endothelial barrier function. 154 The results indicated that cRGD-coated stents showed superiority in reinforcing endothelial integrity and maintaining the semi-permeability compared to commercial DES (Fig. 10B).…”
Section: Current Research Progress On Cardiovascular Stents At the La...mentioning
confidence: 89%
“…Joner et al investigated whether cyclic arginine-glycine-aspartic acid (cRGD)-coated stents that targeted integrin α v β 3 could increase the adhesion of ECs as well as elevate endothelial barrier function. 154 The results indicated that cRGD-coated stents showed superiority in reinforcing endothelial integrity and maintaining the semi-permeability compared to commercial DES (Fig. 10B).…”
Section: Current Research Progress On Cardiovascular Stents At the La...mentioning
confidence: 89%
“…New Zealand White (NZW) rabbits are widely used as an animal model for the study of atherosclerosis. In rabbits, balloon dilation and stenting of major arteries such as the common carotid artery, abdominal aorta, and iliac artery can be used to study the mechanism of injury in ISNA research (63)(64)(65)(66). In addition, implantation of coronary stents in the abdominal aorta of apoE-/-rats is a good model for studying ISR after stent placement and can potentially be used to investigate the mechanisms of injury associated with ISNA (67).…”
Section: Current Status Of In-stent Neoatherosclerosis Research and F...mentioning
confidence: 99%